Dementia in old age: from diagnosis to fatal outcome - N. M. Mikhaylova; O. N. Sokolova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Background: It is well known, that old age dementias steadily grow progressively worse and inevitably lead to fatal outcome. Mortality indices in foreign research largely vary, they are practically absent in domestic scientific studies, and official statistical data on the prevalence of dementia and the cause of death do not reflect the real situation. The Objective of the study was to perform the analysis of completed cases of late age dementias from the materials of observations in Alzheimer’s disease center of the Mental Health Research Center.Patients and Methods: Observational study, using prospective method of out-patient observation of subjects with dementias, who consulted Alzheimer’s disease center in 2007-2016 for the first time, made it possible to obtain reliable data on 217 patients, who died during this period.Results: More than one third of such cases (39%) referred to nosologically various dementias with an early onset of the disease. In more than half of the cases (58%) the cause of death was medical pathology. In the rest of the patients severe or terminal stage of the basic disease was noticed toward the end of life under conditions of home care.Conclusions: Holistic view of the clinical picture of old age dementias (from the onset of the disease till the fatal outcome) is necessary for creation of incidence registers and obtaining of science-based statistical indices of survival, mortality and causes of death. It is necessary to develop measures of assistance to families of patients with the most severe stage of dementias, creation of out-patient and in-patient network of hospices for this contingent of patients.